Characterization of carbon based nanostructures for the detection of tuberculosis - Muñante Palacin, Paulo Edgardo (Pontificia Universidad Católica del Perú, 2017)
Tuberculosis is a leading killing disease worldwide with more than 9 million people a ected per year. Current diagnostic methods exhibit several disadvantages; one of the most promising alternatives to overcome this is the development of nanostructured diagnostic systems which are able to detect molecules associated with certain diseases. Graphene since its discovery has been the focus for the development of these sensing elements due to its excellent electronic properties. In this work, a graphene-based eld e ect transistor (FET) has been developed for tuberculosis DNA detection, in order to set the basis for a diagnostic method that overcomes current limitations. The sensing elements composed of graphene monolayers were manufactured in the stages of annealing of the substrate, addition of the linker and functionalization with the addition of a probe DNA for tuberculosis detection. Additionally, two conditions for the sensing element were generated; one with the addition of a complementary DNA sequence (\DNA Target") and the other with a mismatched DNA sequence (\Non-complementary DNA"). The graphene and the transistor, in each stage of the manufacturing process, were structural, chemical and morphologically characterized by Raman Spectroscopy, Energy Dispersive X-ray Spectroscopy (EDS), Optical Microscopy, Laser Scanning Microscopy (LSM), Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). The results indicated an appropriate functionalization of the graphene surface with the linker, the immobilization of the probe tuberculosis DNA and the hybridization with the corresponding \DNA Target", demonstrated by observation of di erent homogeneous morphologies and an appropriate increase in the roughness in each stage of the manufacturing process. Also by the presence of characteristic peaks of nitrogenous bases and in the variation of graphene bands in the Raman spectrum. On the contrary, the sensor element with the \Non-complementary" showed an agglomeration of the molecules and segregation of salts on a heterogeneous surface. The results of the characterization are consistent with the electronic characteristics previously determined. This investigation contributes to a basis for the development of a tuberculosis detection system based on nanotechnology for clinical application.

La tuberculosis es una de las principales enfermedades mortales en todo el mundo, con más de 9 millones de personas afectadas por año. Los métodos de diagnóstico actuales presentan varias desventajas; una de las alternativas más prometedoras para superar esto es el desarrollo de sistemas de diagnóstico nanoestructurados que son capaces de detectar moléculas asociadas con ciertas enfermedades. El grafeno desde su descubrimiento ha sido un foco para el desarrollo de estos elementos sensores debido a sus excelentes propiedades electrónicas. En este trabajo, se ha desarrollado un transistor de efecto de campo basado en grafeno (FET) para la detección del ADN de la tuberculosis, con el fin de sentar las bases para un método de diagnóstico que supere las limitaciones actuales. Los elementos sensores compuestos de monocapas de grafeno se fabricaron en las etapas de recocido del sustrato, adición del linker y funcionalización con la adición de un probe ADN para la detección de tuberculosis. Adicionalmente, se generaron dos condiciones para los elementos de detección; uno con la adición de una secuencia de ADN complementaria (“DNA Target") y el otro con una secuencia de ADN no complementaria (“Non-complementary DNA"). El grafeno y el transistor, en cada etapa del proceso de fabricación, se caracterizaron estructural, química y morfológicamente por Espectroscopia Raman, Espectrometría de dispersión de energía de rayos X (EDS), Microscopia óptica, Microscopia de Láser de Barrido (LSM), Microscopía Electrónica de Barrido (SEM) y Microscopía de Fuerza Atómica (AFM). Los resultados indicaron una funcionalización apropiada de la superficie del grafeno con el linker, la inmovilización del probe ADN de tuberculosis y la hibridación con el correspondiente “DNA Target", demostrado por la observación de diferentes morfologías homogéneas y un aumento apropiado de la rugosidad en cada etapa del proceso de fabricación. También por la presencia de picos característicos de bases nitrogenadas y en la variación de las bandas de grafeno en el espectro Raman. Por el contrario, el elemento sensor con el “Noncomplementary DNA" mostró una aglomeración de moléculas y segregación de sales sobre una superficie heterogénea. Los resultados de la caracterización son consistentes con las características electrónicas previamente realizadas. Esta investigación contribuye a dar una base para el desarrollo de un sistema de detección de la tuberculosis basado en la nanotecnología para uso clínico.
Keywords: Sensores--Tuberculosis; Materiales nanoestructurados; Grafeno; https://purl.org/pe-repo/ocde/ford#2.05.01